Characterization and Optimization of Triphenylmethane dye ‘Brilliant Green’ Degradation by four indigenous bacterial species: (Retracted) - Md. Delwar Hossain; Shoma Dutta; Md. Nural Anwar (Tropical Life Sciences Research, 2015)
Notice of RetractionThe Tropical Life Sciences Research herewith announces its decision to retract article Characterization and Optimization of Triphenylmethane dye ‘Brilliant Green’ Degradation by four indigenous bacterial species (Md. Delwar Hossain, Shoma Dutta and Md. Nural Anwar) which was scheduled for publication in Volume 26, Issue 2, 2015. The decision is made upon the basis of redundant publication.The journal also wishes to reiterate the importance of adherence to it's author's guideline, which specifically outlines that: Manuscripts submitted for publication must be original, previously unpublished (except in the form of an abstract or as part of a published lecture or academic thesis), and not under consideration for publication elsewhere. Its publication must be approved by all Authors and tacitly or explicitly by the responsible authorities where the work was carried out, and that, if accepted, it will not be published elsewhere in the same form, in English or in any other language, without the written consent of the publisher, Penerbit Universiti Sains Malaysia (PUSM).